Violence and History: Historic evolution of the representations of violence - Wormser, Gérard (Sens public, 2008)
Violence is a relationship, not a "thing"; nor does it submit to typologies. Nevertheless, that does not mean that violence cannot be studied and its present-day occurrences located, writes Gérard Wormser. The exercise of imagined history is probably one of the best antidotes to violence.